2018
DOI: 10.1016/j.bone.2018.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of type H vessels and osteoblasts by enhanced preosteoclast platelet-derived growth factor type BB attenuates glucocorticoid-induced osteoporosis in growing mice

Abstract: Survival of chronic diseases in childhood is often achieved utilizing glucocorticoids, but comes with significant side effects, including glucocorticoid-induced osteoporosis (GIO). Knowledge of the mechanism of GIO is limited to the adult skeleton. We explored the effect of genetic loss and inhibition of cathepsin K (Ctsk) as a potential treatment target in a young GIO mouse model as genetic loss of cathepsin K results in a mild form of osteopetrosis secondary to impaired osteoclast bone resorption with mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 55 publications
(87 reference statements)
6
56
0
Order By: Relevance
“…GCs can impair both processes. In our published model, prednisolone 10 mg/m 2 /day impaired bone volume, but not growth . Increasing prednisolone to 20 mg/m 2 /day resulted in more significant osteotoxic effects without mortality.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…GCs can impair both processes. In our published model, prednisolone 10 mg/m 2 /day impaired bone volume, but not growth . Increasing prednisolone to 20 mg/m 2 /day resulted in more significant osteotoxic effects without mortality.…”
Section: Resultsmentioning
confidence: 67%
“…We and others have reported that GCs are associated with a decline in bone vasculature . However, how GCs disrupt the steps of angiogenesis/blood vessel maintenance remains unknown.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Osteoporosis is a disease of the bones, in which the rate of bone resorption by osteoclasts exceeds the rate of bone formation by osteoblasts (41). The therapeutic strategy for treating patients with osteoporosis is straightforward: Either decrease the activity of osteoclasts with bisphosphonates and estrogen-associated compounds or increase the activity of osteoblasts with parathyroid hormones (42).…”
Section: Discussionmentioning
confidence: 99%